2015
DOI: 10.1002/polb.23956
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and mechanical behavior of montmorillonite grafted block copolymer brushes

Abstract: Here we report the phase behavior of a family of montmorillonite (MMT) block copolymer brushes (MBBs), a novel class of polymer nanocomposites. MBBs are comprised of discrete MMT platelets encapsulated with block copolymer brushes. These MBBs were synthesized via surface-initiated atom transfer radical polymerization using halogenated alkylammonium surfactants to localize initiation sites on the clay surfaces. Two styreninc MBB systems-poly(styrene-b-n-butyl acrylate) and poly(styrene-b-t-butyl acrylate)-were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…14,[16][17][18] Modification of montmorillonite clays by grafted polymer brushes is an alternative approach to the traditional method of modification by organosilanes. [19][20][21] This method involves the covalent attachment of polymer chains to the clay surface through a process called "grafting." In this approach, a suitable monomer or initiator is first covalently attached to the clay surface, typically through a chemical reaction with the hydroxyl groups present on the surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[16][17][18] Modification of montmorillonite clays by grafted polymer brushes is an alternative approach to the traditional method of modification by organosilanes. [19][20][21] This method involves the covalent attachment of polymer chains to the clay surface through a process called "grafting." In this approach, a suitable monomer or initiator is first covalently attached to the clay surface, typically through a chemical reaction with the hydroxyl groups present on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…There are some advantages to this approach, including: covalent bonding of the modifier to fillers; greater control over surface properties; improved dispersion of the modified fillers in the polymer matrix; and improved mechanical properties of the clay. [19][20][21] However, there are also some potential drawbacks to this approach, including: first, the complexity of the modification process, which requires careful control of reaction conditions and purification steps. Second, the modification of montmorillonite clays by grafted polymer brushes may be difficult to scale up for large-scale production, as the reaction conditions and kinetics may be more difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great efforts have been devoted to fabricating toroidal nanostructures through the self‐assembly of rationally designed blocks . In many cases, toroidal block copolymer micelles are constructed from cylindrical micelles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great efforts have been devoted to fabricating toroidal nanostructures through the self-assembly of rationally designed blocks. [12][13][14][15] In many cases, toroidal block copolymer micelles are constructed from cylindrical micelles. For examples, Yu and Jiang reported how cylindrical micelles changed to rings under shear flow.…”
mentioning
confidence: 99%
“…123,126,145 Recently our group has observed that surface-initiated polymerization (SIP) could result in high graft densities to form brush regime and the resultant steric forces could also result in highly exfoliated nanocomposites. 115,116,131 Based on the type of processing technique being used, different degrees of mixing for polymer and clay could be achieved resulting in mainly three types of structures: phase separated, intercalated or exfoliated structures as visualized in figure 5.1. Depending on the type of polymer, layered silicate,polymerization chemistry and degree of dispersion of clay expected, different approaches for SIP could be employed.…”
Section: Introductionmentioning
confidence: 99%